Fresno County Bar Association Luncheon with Bruce Spaulding - Watkins, Howard::::::::: (1987)
CAO Bruce Spaulding speaking on "The Budget Crisis Facing the Fresno County Justice System" 1987 Fresno County Bar Association President Howard Watkins and 1986 Fresno County Bar Association President Judy Soley seated